Coli bond: A dual-function encryption system for secure information storage and transmission by microorganisms - Xuefeng Xiao; Yunuo Song; Jingxuan Hu; Jinchen Han; Wanbin Xing; Chang Liu (PLoS ONE, 2025)
With global data expected to reach 175 zettabytes by 2025, traditional storage methods face unprecedented challenges, including security risks, limited durability, and high maintenance costs associated with centralized infrastructure. While DNA-based storage systems have demonstrated high density and chemical stability, most existing methods focus primarily on static storage, lacking effective strategies for secure and controllable information transmission. Coli Bond offers a revolutionary approach by combining the molecular precision of DNA storage with the controllable dynamics of synthetic biology, providing an innovative platform for data encryption and storage. In this system, controllable dynamics refer to information transfer regulated by caffeine concentration and temperature. The system leverages synthetic biology to engineer an auxotrophic Escherichia coli strain with a caffeine degradation pathway, enabling precise control of information transfer through conditional growth. A temperature-sensitive self-destruction mechanism ensures irreversible destruction of stored information under specific conditions, preventing unauthorized access and enhancing data security. Experimental validation demonstrated the system’s stability and reliability under various real-world conditions, including survival and function in commercial beverages, during transmission cycles, and under temperature variation. The results confirmed high transmission efficiency during initial contact and a rapid decline in strain viability after multiple transfers, providing an inherent layer of security. By integrating the high density of DNA storage with the dynamic control capabilities of synthetic biology, “Coli Bond” offers a secure and adaptable platform for the storage and transmission of DNA-encoded information, paving the way for future advancements in information storage and transmission technologies.